Polymer Based Directional Coupler Thermooptic Optical Switch - Mohd Supa'at, Abu Sahmah; Mohammad, Abu Bakar; Mohd. Kassim, Norazan (Penerbit UTM Press, 2004)
The optimization of 2°—2 polymer based directional coupler (DC) thermooptic (TO) optical switch (DCTOPS) using Prometheus software has been demonstrated. The coupling length variations as a function of waveguide dimension, waveguide gap, and effective index difference have been studied. The position of the electrode heater, which maximizes the effective index difference between branches have been optimized. With the index contrast of 0.005 between the core and the cladding, the crosstalk level of –40 dB and –37 dB for the cross state and the bar state of TO switch can be achieved respectively.